MANAJEMEN STRATEGI SYARI’AH PADA PELAYANAN HOTEL FAMILY NUR DALAM MENINGKATKAN KEPUASAN PELANGGAN - Ummal Khoiriyah; Zainuddin (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
The hotel business is quite rife in Indonesia, almost all provinces in this country already have five-star hotels. Many of these hotels were simply managed lodgment which has been developed into hotels. Hotel Family Nur is one of the hotels located in Sumenep. This research used a qualitative method. Sources of data in this study consisted of primary data and secondary data. Data collection techniques in this study were observation, interviews, and documentation. The conclusion of this study are the implementation of shari'ah strategy management at Hotel Family Nur, Sumenep Regency applies noble character which includes 3S (Senyum, Sapa, Salam/ Smile, Greet, Greetings) fairness, friendship, patience and courtesy. Several factors that support service at Hotel Family Nur, Sumenep Regency, including: the promotions offered and the strategic location. While the factors that contradict service are: hotel competition, competitive prices and incomplete facilities.